PENGARUH TAX MANAGEMENT PADA KUALITAS LABA DAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - I Putu Edy Arizona; I Nyoman Kusuma A Adnyana Mahaputra; Ni Komang Anggreni (Universitas Pendidikan Nasional, 2017)
The aim of this study is to examine effect of tax management to earning quality in Indonesian manufacturing company listed in Indonesian Stock Exchange between year 2008 and 2013. This study also examine moderating effect of managerial ownership and institutional ownership influence relationship between tax management and earning quality. The statistical method that used is moderated regression analysis.The results show that tax management have negative influence to earning quality. Where as there is no interaction managerial ownership in relation between tax management and earning quality. But institutional ownership is moderated in relation between tax management and earning quality.Keywords: Earning quality, tax management, managerial ownership, institutional ownership.